Ekstraksi Pigmen Betasianin Umbi Bit Merah (Beta Vulgaris L) sebagai Pewarna Rambut Merah Alami dengan Zat Pengikat Mordan Jeruk Nipis (Citrus Aurantifolia) - Tia Mauliza; Elwina Elwina; Irwan Nurdin (Politeknik Negeri Lhokseumawe, 2023)
Beetroot (Beta vulgaris L) apart from being good for consumption, is also good for use as a natural food coloring and cosmetic preparation. This research aims to make hair dye cosmetics from natural ingredients with a number of benefits that can increase beauty, but do not have side effects on the health of the user or the environment, by using beetroot plants as the main ingredient for the dye, and mordant which is an important component for strengthening the bond between dyes and fibers to prevent fading using lime (Citrus aurantifolia). Extraction of beet tubers was carried out using 70% ethanol solvent using the maceration method. Maceration is carried out for 3x24hours. This research used varying volumes of beetroot 2ml, 4ml, 6ml, 8ml and 10ml, with varying volumes of lime as mordant, namely 0.5ml, 1ml, 1.5ml, 2ml and 2.5ml. The research results showed that the best hair dye with a composition of 10ml of beet root extract with a volume of 2ml and 2.5ml of lime had a pH of 6.20 and 6.12 in accordance with the scalp pH standard, namely 4-6.5 in according to SNI 06-2692-1992, test value the color stability during washing changes on average in the 4th washing, the irritation test value is negative for redness, itching and swelling, indicating that the hair dye preparation does not irritate the skin, the organoleptic test value has an average value for color, aroma and texture of 1.82 and the value of absorbed wadar content of betacyanin pigment was R(Red)123=48.24%.